Penggunaan pupuk kompos dan bioboost dalam meningkatkan pertumbuhan dan hasil tanaman bawang daun - Tini Rambu Jola Piras; Yohanes Parlindungan Situmeang; Ketut Agung Sudewa (Fakultas Pertanian, Universitas Warmadewa, 2018)
The purpose of this study was to determine the effect of compost and bioboost doses and their interactions in increasing the yield of leaf onion. This study used a randomized block design (RBD) factorial pattern. The first factor, the compost treatment consisted of 4 levels, namely: without compost, 10 tons ha-1, 20 tons ha-1, and 30 tons ha-1. The second factor, the bioboost fertilizer treatment consisted of 4 levels, namely: without bioboost, 5 cc L-1, 10 cc L-1, and 15 cc L-1, thus there were 16 combination treatments and repeated 3 times so that 48 experimental polybags were needed. The results showed that the compost treatment and the treatment of inter-compost interactions with bioboost had no significant effect on all observed variables. The treatment of bioboost has a very real effect on all observed variables except for the fresh weight of economic results that have a significant effect and the maximum number of leaves has no significant effect. Giving compost at various different dosage levels was not significant, but the compost dose of 30 tons ha-1 yielded the most economical oven dry weight of 1.20 g which increased by 20% compared to yield without compost, namely 1.00 g. The treatment of Bioboost 15 cc L-1 gave the highest oven dry yield of 1.46 g which increased by 80.25% when compared with the lowest value in the treatment without bioboost 0 cc L-1 which was 0.81 g.